Correlation between C677T and A1298C MTHFR polymorphisms and non-obstructive azoospermia in Bulgarian patients - Svetlana Yovinska; Mariela Hristova-Savova; Yuri Bachvarov; Rumen Nikolov; Ivanka Dimova (Pensoft Publishers, 2024)
We have analyzed the following polymorphisms: C677T (rs 1801133) and A1298C (rs 1801131) in the methylenetetrahydrofolate reductase (MTHFR) gene in Bulgarian patients with non-obstructive azoospermia, attending reproductive clinics. We have compared the allele and genotype frequencies of both the MTHFR C677T and A1298C polymorphisms in our population to the European population and to a Bulgarian control group (n = 350). The results of our research have revealed a trend for a significantly higher frequency of the homozygote C/C genotype of MTHFR A1298C polymorphism in comparison to the European and Bulgarian controls (p < 0.08). The prevalence of the C/C homozygotes can be accepted as a risk factor for the development of non-obstructive azoospermia, especially in addition to other external and internal factors-diet, vitamin intake, other genetic polymorphisms or mutations in the genes involved in spermatogenesis.